Advanced surface coating techniques for modern industrial applications - Roy, Supriyo; Bose, Goutam Kumar, 1970- (Engineering Science Reference, an imprint of IGI Global, 2021)
"This book contains research on trends in surface coating materials, deposition techniques, properties of coated materials, and their applications in engineering and industrial fields"--